2015
DOI: 10.1371/journal.pone.0118286
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Responses of Differentiated Asthmatic Human Airway Epithelial Cultures to Rhinovirus

Abstract: ObjectivesHuman airway epithelial cells are the principal target of human rhinovirus (HRV), a common cold pathogen that triggers the majority of asthma exacerbations. The objectives of this study were 1) to evaluate an in vitro air liquid interface cultured human airway epithelial cell model for HRV infection, and 2) to identify gene expression patterns associated with asthma intrinsically and/or after HRV infection using this model.MethodsAir-liquid interface (ALI) human airway epithelial cell cultures were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
66
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(79 citation statements)
references
References 45 publications
12
66
1
Order By: Relevance
“…CCL5 is the dominant chemoattractant present in HRV-15 CM, although CXCL8 may also contribute. These data, together with earlier reports that HRV infected epithelial cells show expression of genes related to airway remodeling (33), and release a number of growth factors and matrix proteins linked to airway remodeling (34)(35)(36), further support the concept that recurrent HRV infections may contribute to the initiation and progression of airway remodeling in asthma. Future studies will need to determine if the current observations are relevant to cells obtained from asthmatic subjects (both children and adults), while clinical studies of either naturally-acquired or experimental HRV infections will confirm whether these observations occur in vivo.…”
Section: Hrv-induced Asmc Migration Is Mediated At Least In Part VIsupporting
confidence: 81%
“…CCL5 is the dominant chemoattractant present in HRV-15 CM, although CXCL8 may also contribute. These data, together with earlier reports that HRV infected epithelial cells show expression of genes related to airway remodeling (33), and release a number of growth factors and matrix proteins linked to airway remodeling (34)(35)(36), further support the concept that recurrent HRV infections may contribute to the initiation and progression of airway remodeling in asthma. Future studies will need to determine if the current observations are relevant to cells obtained from asthmatic subjects (both children and adults), while clinical studies of either naturally-acquired or experimental HRV infections will confirm whether these observations occur in vivo.…”
Section: Hrv-induced Asmc Migration Is Mediated At Least In Part VIsupporting
confidence: 81%
“…Recent findings, that epithelial cells from asthmatics cultured ex vivo showed lower mRNA expression of CDHR3 than cells from non‐asthmatics, agree with our findings in peripheral leukocytes in preschool children with wheezing compared with healthy children. Interestingly, they also showed that the expression was further reduced at RV infection with RV A16 and the level correlated with RV infection .…”
Section: Discussionsupporting
confidence: 92%
“…CDHR3 subcellular localization has not been mapped yet; however, high level of its expression was found in ciliated cells in differentiated airway epithelium [Griggs et al ., manuscript in preparation]. Recent RNA-seq analysis of RV-A16 infected ALI cultures found that CDHR3 mRNA expression at baseline was slightly lower in asthmatic epithelial cells compared to non-asthmatic cells ( p = 0.02), however, the CDHR3 genotype was not provided for these donors [90]. Interestingly, in contrast to ICAM-1 and LDLR, CDHR3 expression was further decreased upon viral infection and its reduction was highly correlated with viral infection (Pearson correlation p -value = 1.6 × 10 −4 ) indicating different regulatory mechanisms.…”
Section: Rhinovirus Receptors and Entry To Host Cellsmentioning
confidence: 99%
“…Interestingly, in contrast to ICAM-1 and LDLR, CDHR3 expression was further decreased upon viral infection and its reduction was highly correlated with viral infection (Pearson correlation p -value = 1.6 × 10 −4 ) indicating different regulatory mechanisms. Rhinovirus-induced disruption of the barrier function of airway epithelial cells cultured at ALI along with downregulation of some tight and adherens junction mRNAs and proteins have been also documented [90–92]. …”
Section: Rhinovirus Receptors and Entry To Host Cellsmentioning
confidence: 99%